2023
DOI: 10.1002/alz.13354
|View full text |Cite
|
Sign up to set email alerts
|

Use of the patient portal among older adults with diagnosed dementia and their care partners

Abstract: INTRODUCTIONCare partners are at the forefront of dementia care, yet little is known about patient portal use in the context of dementia diagnosis.METHODSWe conducted an observational cohort study of date/time‐stamped patient portal use for a 5‐year period (October 3, 2017–October 2, 2022) at an academic health system. The cohort consisted of 3170 patients ages 65+ with diagnosed dementia with 2+ visits within 24 months. Message authorship was determined by manual review of 970 threads involving 3065 messages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
(129 reference statements)
1
3
0
Order By: Relevance
“…Our analysis of patient portal messages of all older adults, and PLWD specifically, found that care partners actively send messages with content relevant for care partner identification, documentation, and support 6,7 . Our findings reinforce high nonpatient use of the patient portal which most often occurs with patient log‐on credentials.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our analysis of patient portal messages of all older adults, and PLWD specifically, found that care partners actively send messages with content relevant for care partner identification, documentation, and support 6,7 . Our findings reinforce high nonpatient use of the patient portal which most often occurs with patient log‐on credentials.…”
Section: Discussionsupporting
confidence: 62%
“…Patient‐level demographic and health characteristics and portal use were extracted directly from the electronic health record. This study was approved by the local Institutional Review Board (IRB00303190) and the cohort is further described elsewhere 6,7 . Dementia diagnosis was operationalized following Grodstein 27 which requires two or more claims with dementia ICD‐10 codes at least 7 days apart, or one instance from a home health, hospice, rural health clinic, critical access hospital, or Federally Qualified Health Center (FQHC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…using the patient's credentials. [7][8][9][10] Accessing patient records in this way, while convenient, can impact patient autonomy and can confuse clinicians who may not know with whom they are communicating. 7 Further, clinicians may not be confident that the care partner has the patient's permission to use the portal or communicate with the care team on their behalf.…”
Section: Accepted Manuscriptmentioning
confidence: 99%